2013
DOI: 10.1371/journal.pone.0073193
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deposition following Chronic Myocardial Infarction as a Substrate for Cardiac Electrical Anomalies: Initial Findings in a Canine Model

Abstract: PurposeIron deposition has been shown to occur following myocardial infarction (MI). We investigated whether such focal iron deposition within chronic MI lead to electrical anomalies.MethodsTwo groups of dogs (ex-vivo (n = 12) and in-vivo (n = 10)) were studied at 16 weeks post MI. Hearts of animals from ex-vivo group were explanted and sectioned into infarcted and non-infarcted segments. Impedance spectroscopy was used to derive electrical permittivity () and conductivity (). Mass spectrometry was used to cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…20 It is well known that iron overload could cause cardiomyopathy with clinical manifestations, including decreasing the cardiac ejection fraction and arrhythmia. [37][38][39] Acidic environments prompt the transformation of iron from the oxidation state (Fe 3+ ) to the reduced state (Fe 2+ ), resulting in the generation of oxygen free radicals. Therefore, the toxic effect of myocardial iron is dynamic and is increased in the presence of metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…20 It is well known that iron overload could cause cardiomyopathy with clinical manifestations, including decreasing the cardiac ejection fraction and arrhythmia. [37][38][39] Acidic environments prompt the transformation of iron from the oxidation state (Fe 3+ ) to the reduced state (Fe 2+ ), resulting in the generation of oxygen free radicals. Therefore, the toxic effect of myocardial iron is dynamic and is increased in the presence of metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mather et al 25 showed that patients with hemorrhagic infarction have prolonged filtered QRS duration, which they associated with increased late-arrhythmogenic risk. Recent canine studies have also confirmed that hemorrhagic infarctions can lead to chronic iron deposition 26 and that post infarction iron can preferentially alter electrophysiology indices within the infarcted heart 27 . Moreover, forensic studies utilizing clinical cardiac magnetic resonance imaging (CMR) have shown that SCD victims with chronic MI consistently have hypointense zones in the scarred myocardium in T 2 -weighted CMR 28, 29 , which is consistent with iron accumulation.…”
mentioning
confidence: 89%
“…Instead, erythrocyte compounds, such as haemoglobin, or iron deposits can be stained with a haemoglobin antibody or Perl's Prussian blue staining, which stains ferritin deposits. 18,20,109 Erythrocytes can also be labelled with radioisotopes or erythrocyte extravasation can be mimicked by injection of radioactive or gold-labelled microspheres, and can be visualized using spectroscopy. 47,51,[110][111][112][113] Predicting the risk of haemorrhage…”
Section: Experimental Imaging Studiesmentioning
confidence: 99%
“…13,[15][16][17] Biodegradation of haem molecules leads to deposition of cytotoxic levels of iron in the myocardium. This accumulation triggers macrophage influx and, consequently, a chronic phase involving the generation of reactive oxygen species, [18][19][20] necrosis, inflammation, and fibrosis. Prevention of microvascular injury and intramyocardial haemorrhage in the acute phase could, therefore, be of benefit to patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%